TRADITIONAL AND ISLAMIC FINANCE: ASPECTS IN ENSURING SUSTAINABLE ECONOMIC GROWTH IN THE REGIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article examines the role of traditional and Islamic finance in promoting sustainable economic growth in different regions. A literature review and comparative analysis is conducted to assess the key aspects of these financial systems that contribute to economic stability and long-term prosperity. The results show that the risk-sharing partnership model, prohibition on speculation, and emphasis on tangible assets in Islamic finance, along with the community-based lending and local investment focus of many traditional financial institutions, help foster entrepreneurship, protect against economic shocks, and encourage productive investment in regional economies.